Relation between insect damage and yield of indian mustard (Brassica juncea) sown on different dates in Gujarat - PATEL, M G; PATEL, J R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted dming winter season (rabi) 1988-89 to 1992-93 to study the effect of different dates of sowing indian mustard [Brassica juncea (L.) Czernj. & Casson] on incidence of pests and crop yield. The crop sown in the third week of September and first week of October had significantly lower population of mustard sawfly [Athalia lugens proxima (Kliig.)] and aphid [Lipaphis erysimi (Kalt.)], which reflected on the yield and gave higher yield than the crop sown in the third week of November.